Natural conditions as an one factor belonging to war campaigns in Thietmar’s and Gallus Anonymous’s narration. Appendix to first Piast’s policy - Wybranowski, Dariusz (Armia kontra natura, 2020)
Author’s main scientific base for present publication of are such medieval sources: Chronicle of Bishop Thietmar of Merseburg and later, Polish Chronicle of Gallus Anonymous. The main questions of ananalysis were: are a or long distance (also transport, logistic problems and food for medieval armies), the war campaigns leading in the forests and in the mountains, also rivers and their place in medieval campaigns. For author is a an important question – level of presence all this elements of a natural enviromnents in both chronicles for description of campaigns and battles. – Are for these medieval writers forests, rivers, lakes, mountains is an integral parts of chronicle’s battle narration or only an indirect information? In this article, an author has trying to prove that in Gall Anonymous narration, the prince Boleslaw the Wrymouth is a great winner (not only as a militar leader) of fight with wild nature (crossing the Sudety Mountains with army during war campaigns against Czech’s and Moravians, a very long way across the deep forests of Pomerania, and in the land of Prussians). For bishop Thietmar, an occasion to presenting the factor of wild natural environment are the wars against prince Boleslaw the Brave (1002–1018), and the great battle of Bug River (1018) with great prince Jaroslav the Wise from Kiev. For anannalist from Saxonia the main element of war descriptions in some cases are big rivers and as a danger. A good exampleis a description of the battle in deepforest, ended as a collapse of emperor Henry’s the Second army in the land of Dziadoszanie tribe’s (Silesia) in 1015. But for Thietmar, some informations concerned with natural conditions in his narration are only indirectin formation, not a main element. The situation is quite different in Gall Anonymous’s narration. Deep forests, rivers, high and dangerous mountains are integral part of relations about war campaigns of Polish kings and princes from Piast dynasty. A longride to Kołobrzeg (Pomerania) during „five days” (1103) is a good example for Gallus of prince’s Boleslaw the Wrymouth victory against nature and a long distance. The war of prince Wrymouth’s against Emperor Henry the Fifth (1109) and German army (as the invaders) is one exemplification more for „partisan fighting” in wild forest. One of the most interesant episode in Gallus Anonymous narration’s is a campaign of Boleslaw the Second (Audacious) against the Pomeranians (date unknown). In the deep river many of his knights in armors were sunk. This relations was anexample as a morality play (too brave king and their knights) to punishment for a mad reckleness. A great bloody battle near Gopło Lake (1097) is an example of „God’s judgement” and the punishment for in habitants of Kruszwica stronghold. The number of exemplifications concerned with natural conditions is quite greater in Gallus’s Chronicle than in Thietmar’s. These relations having not only meaning as a simply information. Some more elements of Anonymous’s Chronicle are: classical erudition of an author and the great literary value.